Black soldier fly larvae oil (Hermetia illucens L.) calcium salt enhances intestinal morphology and barrier function in laying hens - Anas, Muhsin Al; Aprianto, Muhammad Anang; Akit, Henny; Muhlisin; Kurniawati, Asih; Hanim, Chusnul (Elsevier, 2024)
This study aimed to determine the influence of black soldier fly larvae oil calcium salt (BSFLO-SCa) supplementation on performance, jejunal histomorphology and gene expression of tight junctions and inflammatory cytokines in laying hens. A total of 60 ISA Brown laying hens (40 wk of age) were divided into 3 treatment groups, including a control group fed a basal diet (T0) and basal diets supplemented with 1% (T1) and 2% (T2) of BSFLO-SCa. Each treatment group consisted of 5 replicates with 4 laying hens each. Results showed that 1% and 2% BSFLO-SCa supplementation significantly reduced (P < 0.05) feed conversion ratio (FCR), while egg weight (EW) increased (P < 0.05). The inclusion with 2% increased (P < 0.05) both egg production (HDA) and mass (EM). The addition of 1% and 2% BSFLO-SCa significantly increased (P < 0.05) villus height (VH) and villus width (VW), while crypt depth (CD) significantly increased (P < 0.05) with 2% BSFLO-SCa. The tight junction and gene expression of claudin-1 (CLDN-1), junctional adhesion molecules-2 (JAM-2), and occludin (OCLN) were significantly upregulated (P < 0.05) with 2% BSFLO-SCa. The pro-inflammatory cytokines and gene expression of interleukin-6 (IL-6) was significantly downregulated (P < 0.05) with the addition of BSFLO-SCa, while gene expression of interleukin-18 (IL-18), toll-like receptor 4 (TLR-4), and tumor necrosis factor-α (TNF-α) were downregulated with 2% BSFLO-SCa. On the other hand, the anti-inflammatory cytokines and gene expression of interleukin-13 (IL-13) and interleukin-10 (IL-10) were significantly upregulated (P < 0.05) at 2% BSFLO-SCa. In conclusion, dietary supplementation with 2% BSFLO-SCa improved productivity, intestinal morphology and integrity by upregulating tight junction-related protein of gene expression of laying hens. In addition, supplementation with BSFLO-SCa enhanced intestinal immune responses by upregulating anti-inflammatory and downregulating pro-inflammatory cytokine gene expression.